The macroeconomic effects of forward communication - Leif Brubakk; Saskia ter Ellen; Ørjan Robstad; Hong Xu (Norges Bank, 2019)
This paper provides an empirical assessment of the power of forward guidance at different horizons, shedding new light on the strength of the "forward guidance puzzle". Our identification strategy allows us to disentangle the change in future interest rates stemming from deviations from the systematic part of monetary policy ("target" and "forward guidance" shocks) and changes in future interest rates that are due to unanticipated revisions in the central bank's economic outlook ("information" shocks). This enables us to make a qualitative assessment of the relative importance of forward guidance. We investigate to what extent the horizon of guidance matters for its macroeconomic effects, and find that the more forward the shock is, the weaker is its impact on output and inflation. This runs contrary to the prediction from standard New Keynesian models that the power of forward guidance increases with its horizon.
hdl:11250/2652993
Keywords: E43; E44; E52; E58; 330; monetary policy; forward guidance puzzle; high-frequency identification; structural VAR; central bank information